Initial psychometric evaluation of the European Portuguese version of the Lincoln Canine Adaptability Resilience Scale - J. C. Alves; Ana Santos; P. Jorge; T. Mendonça (PLoS ONE, 2025)
Objective Dogs face a variety of stressors in their lives, either as companion or as working animals, from novel situations and challenges, to visits to the vet, kenneling, or transportation. Some individuals have personal characteristics that allow them to cope with adversity and develop positive adaptations. The Lincoln Canine Adaptability Resilience Scale (L-CARS) was developed to assess this ability. This study aimed to validate a European Portuguese version of the Lincoln Canine Adaptability Resilience Scale. Patients and methods Information from 182 dogs was collected. The English version of the L-CARS was translated into Portuguese, and this version was back-translated until a unified version was obtained. Canine handlers, native Portuguese speakers, completed a copy of the translated Portuguese version of the L-CARS. Validity testing was performed with the Kaiser-Meyer-Olkin measure of sampling adequacy. Extrated values were assessed based on Eigenvalue and scree-plot analysis. Internal consistency was tested with Cronbach’s α. The correlation between items was determined using Spearman’s rank correlation coefficient. Results Kaiser-Meyer-Olkin factor analysis was 0.83. The factor analysis model identified five factors with an eigenvalue greater than 1, accounting for 67.56% of the variance. Commonalities ranged between 0.86 and 0.29. Cronbach’s α was 0.81. All components showed positive correlation with the overall score (p < 0.01 for both). Conclusions The study presented criterion and construct validity of the European Portuguese version of the L-CARS. It is a step in providing a broader Portuguese-speaking population and clinicians with a validated and accessible tool to evaluate patients. Further studies are required.